Ablation of Rotor Domains Effectively Modulates Dynamics of Human: Long-Standing Persistent Atrial Fibrillation. (December 2017) - Calvo, David; Rubín, José; Pérez, Diego; Morís, César
Abstract : Background: In human long-standing persistent atrial fibrillation, rotors potentially explain atrial fibrillation maintenance, but their ablation remains controversial. We aimed to explore original phase/frequency mapping methods to locate rotors and track changes induced by their ablation. Methods and Results: Thirteen patients with long-standing persistent atrial fibrillation (duration, 12–72 months) underwent phase/frequency mapping (Hilbert/Fourier transforms; CARTO-Finder) of the left and right atria (PentaRay catheter). A rotor domain was defined as an area displaying at least 3 consecutive rotations. Ablation was performed by circumferential pulmonary vein isolation plus linear ablation of extrapulmonary rotor domains. We identified 19 rotor domains in 10 patients (1.8±1.1 per patient; 7 in the right atrium versus 12 in the left atrium; 15 extrapulmonary). Overall, rotor domains (9.2±2.2 rotations) displayed higher frequency of activation (6.41 Hz; 95% confidence interval, 6.24–6.57) than nonrotor domains (6.17 Hz; 95% confidence interval, 6.1–6.23; P =0.021), with interatrial frequency gradients established by the spatial location of the rotor domain ( P =0.016). Fibrillatory conduction was suggested as a decrease in the frequency of the slower atria after ablation close to main interatrial conduction fascicles ( P =0.035). Ablation of rotor domains (ablation line, 3.5±0.9 cm) effectively decreased the frequency of activation in both ipsilateral and contralateral atria ( P <0.05 for both), whereas ablation of nonrotor domains did not. Acute conversion to sinus rhythm was observed in 2 patients after ablation of rotor domains. At 1-year follow-up, 70% remained in sinus rhythm (85% out-of-antiarrhythmic drugs). Conclusions: Rotor domains appropriately explain long-standing persistent atrial fibrillation physiology at its frequency content. Their ablation effectively modifies dynamics on restricted ablation. Abstract : Supplemental Digital Content is available in the text.